To avenge a ranger [large type] - Griffin, James J., 1949- (A Texas Ranger Sean Kennedy Novel, 2021)
"A legendary lawman lies dead, cut down by a bushwhacker's bullet, and it's up to Texas Ranger Sean Kennedy to track down the killer and bring him to justice. But at every step in his search, Kennedy finds that the trail to the truth leads farther and farther into the past . . ."--